Shelf life of rainbow trout fillets hot smoking with different sauces - Inanli, Ayse Gurel; Kuzgun, Nermin Karaton; Coban, Ozlem Emir; Ozpolat, Emine (Ege Univ, Fac Fisheries, 2018)
In this study, products of smoked fish were prepared from rainbow trout (Oncorhynchus mykiss, Walbaum 1792). Smoked fish with different sauce were prepared by targeting an increase in the consumption of trout which has a considerable production potential and is a delicious fish. 4 groups (A, B, C and D) applied with different sauces were prepared in the study. Samples were stored in a refrigerator (4 degrees C) during storage. The aim of the study is to determine the chemical, microbiological and sensorial changes, the shelf life of products during the storage period of products. Study had 2 replicates and analyses had 3 parallels. As a result, the qualities of chemical, microbiological and sensorial of the smoked samples prepared in our study were examined. The evaluation of data showed the shelf life as 14 days for A, 28 days for B, 21 days for C and 35 days for D with sauces. When the data obtained were evaluated, the shelf life was determined as 14 days for A, 28 days for B, 21 days for C and 35 days for D with sauces.
Keywords: Rainbow trout; smoked; different sauce; shelf life